An Ising model with three competing interactions on a Cayley tree - Ganikhodjaev, Nasir; Pah, Chin Hee; Wahiddin, Mohamed Ridza (American Institute of Physics Inc., 2004)
In this paper we consider an Ising model with three competing restricted interactions on the Cay ley tree J2(J3). The translation invariant and periodic Gibbs measures for these models are investigated and the problem of the phase transition in these classes is solved. © 2004 American Institute of Physics.